Developmental psychology I : perceptual and cognitive development - Bremner, J. Gavin; Lewis, Charlie (New York : SAGE Publications, 2005)
Vol. 1. Theoretical perspectives on perception and cogtition -- v. 2. Infant perceptual and cognitive development -- v. 3. Perceptual and cognitive development in childhood